Effects of short-term dietary nitrate supplementation on exercise and coronary blood flow responses in patients with peripheral artery disease - Kim, Danielle Jin-Kwang; Gao, Zhaohui; Luck, Jonathan C.; Brandt, Kristen; Miller, Amanda J.; Kim-Shapiro, Daniel; Basu, Swati; Leuenberger, Urs; Gardner, Andrew W.; Muller, Matthew D.; Proctor, David N. (Frontiers in Nutrition, 2024)
Background: Peripheral arterial disease (PAD) is a prevalent vascular disorder characterized by atherosclerotic occlusion of peripheral arteries, resulting in reduced blood flow to the lower extremities and poor walking ability. Older patients with PAD are also at a markedly increased risk of cardiovascular events, including myocardial infarction. Recent evidence indicates that inorganic nitrate supplementation, which is abundant in certain vegetables, augments nitric oxide (NO) bioavailability and may have beneficial effects on walking, blood pressure, and vascular function in patients with PAD.Objective: We sought to determine if short-term nitrate supplementation (via beetroot juice) improves peak treadmill time and coronary hyperemic responses to plantar flexion exercise relative to placebo (nitrate-depleted juice) in older patients with PAD. The primary endpoints were peak treadmill time and the peak coronary hyperemic response to plantar flexion exercise.Methods: Eleven PAD patients (52-80 yr; 9 men/2 women; Fontaine stage II) were randomized (double-blind) to either nitrate-rich (Beet-IT, 0.3 g inorganic nitrate twice/day; BRnitrate) or nitratedepleted (Beet-IT, 0.04 g inorganic nitrate twice/day, BRplacebo) beetroot juice for 4 to 6 days, followed by a washout of 7 to 14 days before crossing over to the other treatment. Patients completed graded plantar flexion exercise with their most symptomatic leg to fatigue, followed by isometric handgrip until volitional fatigue at 40% of maximum on day 4 of supplementation, and a treadmill test to peak exertion 1 to 2 days later while continuing supplementation. Hemodynamics and exercise tolerance, and coronary blood flow velocity (CBV) responses were measured.Although peak walking time and claudication onset time during treadmill exercise did not differ significantly between BRplacebo and BRnitrate, the diastolic blood pressure response at the peak treadmill walking stage was significantly lower in the BRnitrate condition. Increases in CBV from baseline to peak plantar flexion exercise after BRplacebo and BRnitrate showed a trend for a greater increase in CBV at the peak workload of plantar flexion with BRnitrate (p=0.06; Cohen's d = 0.56).Overall, these preliminary findings suggest that inorganic nitrate supplementation in PAD patients is safe, well-tolerated, and may improve the coronary hyperemic and blood pressure responses when their calf muscles are most predisposed to ischemia.